Pengaruh media karet ban terhadap peningkatan kepercayaan diri dalam melakukan gerak dasar tiger sprong - Raihandi, M.; Suherman, Asep; Kurniawan, Febi (Universitas Hamzanwadi, 2023)
The aim of this research is to find out whether there is a relationship between self-confidence and basic movement skills of tiger sprongs. This research methodology is quantitative and experimental. The population in this study was 35 students. The sampling technique used purposive sampling consisting of 21 men and 9 women. The research instrument uses observation, interviews, lift. Data analysis uses instrument requirements tests, reliability tests, hypothesis tests, normality tests. The results show 0.05, with a coefficient of determination of 0.000, meaning that 93% of students at SMPN 5 West Karawang are more confident in performing basic tiger spong movements due to the use of rubber tires, while 7% are also influenced by other reasons. The increase in students' self-confidence will increase with the intensity of learning the basic tiger fork using 1,000 rubber tires as a medium, in accordance with the simple linear regression equation = 98,462 + 1,000 calculations and data analysis show that there is a significant influence between the variables of the influence of rubber tire media on increasing self-confidence in basic movement abilities of tiger sprong